Clinical relevance of serum lipids in the carcinogenesis of oral squamous cell carcinoma - Ling Qian; Bo Qian; Juanyong Xu; Jingjing Yang; Guoying Wu; Yuping Zhao; Qinglan Liu; Zhiran Yuan; Yuan Fan; Huaiqi Li (BMC, 2023)
Abstract Background Dyslipidaemia is associated with cancers. However, the specific expression of serum lipids in oral potentially malignant disorders (OPMD) and oral squamous cell carcinoma (OSCC) remains unclear, and it remains unknown whether serum lipids are associated with the development of OPMD and OSCC. This study investigated the serum lipid profiles of OPMD and OSCC patients, and the association of serum lipids with the occurrence of OPMD and OSCC. Methods A total of 532 patients were recruited from the Affiliated Hospital of Stomatology, Nanjing Medical University. Serum lipid parameters including total cholesterol (TC), triglycerides (TGs), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), apolipoprotein A (Apo-A), apolipoprotein B (Apo-B), and lipoprotein (a) (Lpa) were analysed, and clinicopathological data were collected for further analysis. Furthermore, a regression model was used to evaluate the relationship between serum lipids and the occurrence of OSCC and OPMD. Results After adjusting for age and sex, no significant differences were observed in serum lipid or body mass index (BMI) between OSCC patients and controls (P > 0.05). HDL-C, Apo-A, and Apo-B levels were lower in OSCC patients than in OPMD patients (P < 0.05); HDL-C and Apo-A levels were higher in OPMD patients than in controls (P < 0.05). Furthermore, female OSCC patients had higher Apo-A and BMI values than males. The HDL-C level was lower in patients under 60 years of age than in elders (P < 0.05); and age was related to a higher risk of developing OSCC. Female patients with OPMD had higher TC, HDL-C, and Apo-A levels than males (P < 0.05); OPMD patients over 60 years of age had higher HDL-C than youngers (P < 0.05), whereas the LDL-C level was lower in elders (P < 0.05). The HDL-C and BMI values of the patients with oral leukoplakia (OLK) with dysplasia were more elevated than those of the oral lichen planus group, and the LDL-C, and Apo-A levels in patients with OLK with dysplasia were decreased (P < 0.05). Sex, high HDL-C and Apo-A values were associated with the development of OPMD. Conclusion Serum lipids exhibited certain differences according to the occurrence and development of OSCC; high levels of HDL-C and Apo-A might be markers for predicting OPMD.